The Poverty of the Foundlings of the Orphanage of Pontevedra (1872-1925) - Rodríguez Martín, Ana María (Madrygal. Revista de Estudios Gallegos, 2020)
This article has a double purpose. The first one is to establish the social enviroment the foundlings of the Inclusa de Pontevedra (the orphanage of Pontevedra) came from and once adults, the circumstancies in which they lived and died. The second aim is to analyze how foundlings were regarded by the society and how their condition of orphans affected them. This study starts with the opening of the institution in 1872 and reaches the end of the anonymous admissions in it in 1925. In order to achieve these aims the clothing and the notes attached to it when the children were abandonned have been analized. Moreover, we have established some features of foundlings in their life as adults taking into consideration their means at birth, their educational levels and jobs they performed. Thorought press articles and the orphanage director’s statements mainly, the social reputation of the foundlings has been also studied. Foundlings’ attempts to find their mothers or relatives have been documented and analysed. We might conclude that foundlings of the Inclusa de Pontevedra as well as those from other institutions were born poor and remained poor until death. The orphanage or any other charity they stayed afterwards failed to improve their lifes’ conditions. Children who were not picked up by their mothers who had left them behind did not have a biological family and because of that they were stigmatized as they were of unknown parents.